PENGETAHUAN DAN PEMAHAMAN AKANPENTINGNYAKEBERSIHAN ALAT VITAL WANITA SEBAGAI PENCEGAH KANKER SERVIKS - Tuasikal M. Amin (Asian Journal of Innovation and Entrepreneurship, 2014)
Because85% of Cancer in the World, which amounted to 273 000 Approximately493,000 with death, occurred in Developing Countries. And Indonesia is having PeriodCervical cancer sufferers secondLargest taxable income after China's. Cervical cancercause problems form of pain and suffering, even Until Death. In addition to infectionscaused by Human Papolomma Virus (HPV), cervical cancer also can be caused becausepersonal hygiene (Cleanliness Self) poorly. Therefore important to review instillawareness of 'public importance Keeping Yourself for review to avoid Danger of cervicalcancer.